(untitled) - Tettoni, Luca Invernizzi (Singapore, 2007)
Vietnam has long captured the imagination of travelers, both real and armchair. It is an appealing country, filled with natural beauty, tranquil village life and fascinating cities. Vietnam also has an inimitable architectural and interior design style, the product of its rich cultural heritage and the various influences of Chinese, French and other Western colonialism. Vietnam Style is an exploration of the balancing act between traditional vernacular design and architecture and the outside influences of colonialism. The unusual and striking new design styles created by melding these elements are a true cultural kaleidoscope of Vietnam today. Chinese-style shophouses, temples with Indian influences, Thai-style palaces, French Colonial civic and domestic buildings, and the variety of tribal and native wooden houses present in Vietnam Style offer an intimate look into the vibrant, yet virtually unknown world of modern Vietnamese architecture and design.
Keywords: Architecture, domestic,Vernacular architecture,Interior decoration; Vietnam,Vietnam,Vietnam